Reversal interest rate and macroprudential policy - Matthieu Darracq Pariès; Christoffer Kok Sørensen; Matthias Rottner (Deutsche Bundesbank, 2021)
Could a monetary policy loosening in a low interest rate environment have unintended recessionary effects? Using a non-linear macroeconomic model fitted to the euro area economy, we show that the effectiveness of monetary policy can decline in negative territory until it reaches a turning point, where monetary policy becomes contractionary. The framework demonstrates that the risk of hitting the rate at which the effect reverses depends on the capitalization of the banking sector. The possibility of the reversal interest rate gives rise to a novel motive for macroprudential policy. We show that macroprudential policy in the form of a countercyclical capital buffer, which prescribes the build-up of buffers in good times, substantially mitigates the probability of encountering the reversal rate and increases the effectiveness of negative interest rate policies. This new motive emphasizes the strategic complementarities between monetary policy and macroprudential policy.
Keywords: E32; E44; E52; E58; G21; 330; Reversal Interest Rate; Negative Interest Rates; MacroprudentialPolicy; Monetary Policy; ZLB